Were Hominins Specifically Adapted to North-Western European Territories Between 700 and 600 ka? New Insight Into the Acheulean Site of Moulin Quignon (France, Somme Valley) - Moncel, Marie-Hélène; Antoine, Pierre; Herisson, David; Locht, Jean-Luc; Hurel, Arnaud; Bahain, Jean-Jacques (Frontiers in Earth Science, 2022)
Current data seem to suggest that the earliest hominins only occupied the Northwest of Europe during favourable climatic periods, and left the area when the climate was too cold and dry, in the same way as Neandertal and even Homo sapiens. However, several sites in England and the North of France indicate that the earliest hominins, possibly Homo antecessor and/or Homo heidelbergensis, could adapt to cool environments and open grasslands without the use of fire. Recent discoveries of Acheulean lithic assemblages in early glacial fluvial deposits at Moulin Quignon in the Somme Valley in the Northwest of France reveal new knowledge on the earliest occupations in north-western territories and indicate hominins’ capacity to live above the c. 45th N. under a cold climate. The site shows evidence of occupations at the beginning of MIS 16 at around 650-670 ka. These findings bring to the forefront the possible ability, flexibility and resilience of Acheulean hominins at around 700 ka to extend to northern territories during transitional climatic periods (interglacial/glacial events), even if the climate was not fully favourable. Recent fieldwork has changed our interpretation of the timing and characteristics of the earliest Acheulean techno-complexes in Western Europe over a large geographical area, from Northwest Europe to the Mediterranean coast. In Western Europe, the earliest evidence, Moulin Quignon, is now dated to a narrow timeframe, between 700-650 ka, and is the northernmost evidence of biface production. This latter is earlier than British Acheulean records. Based on new findings at Moulin Quignon, we explore whether Acheulean traditions and associated new technological abilities could have facilitated the dispersal of hominins in Western Europe over large territories, regardless of climatic conditions. . Changes in behavioural flexibility, and not only phenotypic changes in Homo heidelbergensis groups, have to be investigated. Here, we examine the behavioural and technological abilities of hominins in north-western Europe in light of the available environmental data and compare them to those in southern areas between 700 and 600 ka.